Psychological Patterns in Sexual Relationships: Ukrainian Adaptation of the Multidimensional Sexual Questionnaire - Shyroka, Anastasiia; Zavada, Tetiana (Journal of Education Culture and Society, 2022)
Aim. Human sexuality is an important multidimensional subject for psychological research. However, the study of sexuality remains relatively closed for Ukrainian researchers, primarily due to a lack of valid and reliable measures of sexuality in general, and in particular, measures of psychological patterns in human sexuality. Therefore, the aim of the present study was to validate a self-report English-language tool, the Multidimensional Sexual Questionnaire (MSQ), for the Ukrainian language. Methods. A total of 1113 Ukrainian-speaking participants were administered the MSQ-UA. The MSQ-UA factor structure was measured using EFA and CFA procedures. Alpha and Omega estimates of internal consistency were calculated. The test-retest reliability was established in a five-week time period. The correlations of the MSQ-UA subscales with relevant psychopathology, personality measures and control statements were accomplished to prove the construct validity of the questionnaire. Results. Findings indicated that the MSQ-UA is an eleven-dimensional measure, which is almost identical to the original English-language version. Subscales of the MSQ-UA display acceptable excellent psychometric properties of internal consistency (Alpha and Omega within a range of 0.70 to 0.92). The test-retest reliability over the five-week period was appropriate (r=0.68-0.93). The MSQ-UA subscales demonstrated from moderate to high correlations with relevant measures, and the associations were absent or low in cases when criterion measures were irrelevant to the subscale. Conclusion. The MSQ-UA demonstrated appropriate psychometric properties and may be applied to assess a broad range of psychological patterns in sexual relationships in the Ukrainian-speaking population.